Improving VTE risk assessment and prophylaxis prescribing rate in medical patients: integrating risk assessment tool into the workflow. Issue 2 (14th June 2020) - Preston, Hannah; Swan, Iain; Davies, Lauren; Dummer, Simon; Aravindan, Veiraiah; Beh, Yuan Ye; Lockman, Ann
Abstract : Medical inpatients often have important risk factors for venous thromboembolism (VTE). In our institution, VTE prophylaxis in this group was underused. The main barriers identified were inattention to VTE prophylaxis, competing priorities and lack of confidence in the decision-making. We aimed to improve the rate of VTE prophylaxis use by introducing a paper-based risk assessment tool, with actionable management recommendations within the prescription chart. The rationale was that an assessment tool at the point of prescribing can reduce steps between decision-making and prescribing process, thus promoting confidence and acting as a reminder. A total of 552 prescription charts completed over a period of 29 weeks were examined during the baseline period. In the postintervention period, 871 charts completed over 40 weeks period were examined. The risk assessment tool was completed in 51% of the cases examined in the postintervention period. The introduction of the risk assessment tool was associated with a significant change in the pattern of VTE pharmacological prophylaxis use. The change occurred when the form was made highly visible and enclosed in the prescription chart. The pharmacological prophylaxis use was higher with a completed assessment form than without (mean (SD) 97.5% (7.6%) vs 70.1% (19.4%); p<0.0001). The rate of appropriate prophylaxis decision was 98.2% (SD 5.2%) with a completed assessment form, and 80.7% (SD 17.9%) when it was not used. The qualitative interviews revealed positive themes; many users found it useful, easy and convenient to use. Our data have shown that a paper-based VTE risk assessment tool placed within the prescription chart could substantially improve the rate of appropriate assessment and VTE prophylaxis implementation. This suggests that tool clearly needs to be a seamless integration into the workflow to capture users' attention and mitigate the influence of time perception.